Structure guided design of potential inhibitors of human calcium–calmodulin dependent protein kinase IV containing pyrimidine scaffold. Issue 3 (1st February 2016) - Naz, Huma; Jameel, Ehtesham; Hoda, Nasimul; Shandilya, Ashutosh; Khan, Parvez; Islam, Asimul; Ahmad, Faizan; Jayaram, B.; Hassan, Md. Imtaiyaz
Graphical abstract: Molecule3 in the active site cavity of CAMKIV showing various non-covalent interaction. Highlights: Three potential ligands were docked in the active site cavity of CAMKIV. Several non-covalent interactions are formed between ligands and CAMKIV. All three ligands were synthesized and characterized successfully. Molecule3 is showing very high affinity for the CAMKIV in the nm range. Abstract: Calmodulin dependent protein kinase IV (CAMKIV) belongs to the serine/threonine protein kinase family and considered as an encouraging target for the development of novel anticancer agents. The interaction and binding behavior of three designed inhibitors of human CAMKIV, containing pyrimidine scaffold, was monitored by in vitro fluorescence titration and molecular docking calculations under physiological condition. In silico docking studies were performed to screen several compounds containing pyrimidine scaffold against CAMKIV. Molecular docking calculation predicted the binding of these ligands in active-site cavity of the CAMKIV structure correlating such interactions with a probable inhibition mechanism. Finally, three active pyrimidine substituted compounds (molecules1 –3 ) have been successfully synthesized and characterized by 1 H and 13 C NMR. Molecule3 is showing very high binding-affinity for the CAMKIV, with a binding constant of 2.2 × 10 8, M −1 (±0.20). All three compounds are nontoxic to HEK293 cells up to 50 μM. The cell proliferation inhibition study showed that the molecule3 has lowest IC50 value (46 ± 1.08 μM). The theoretical and experimental observations are significantly correlated. This study reveals some important observations to generate an improved pyrimidine based compound that holds promise as a therapeutic agent for the treatment of cancer and neurodegenerative diseases.